Second Five Year Plan Uttar Pradesh Revised Volume II - Planning Commission (Planning Commission, 1959)
This is multi-purpose project both for irrigation and power and has boon so compiled that the irrigation part can be taken up independently of the power part. In the Second Five-Year Plan provision has been made for the installation of flood gates which will increase the capacity of the installation of flood gates which will increase the capacity of the reservoir to 40,000 m.c.ft. This additional Storage will be used for expanding irrigate n still further by constructing reservoir to 40,000 m.c.ft. This additional Storage will be used for expanding irrigate n still further by constructing used for expanding irrigate n still further by constructing now channels in the same Dabs in which channel of the 1st now channels in the same Dabs in which channel of the 1st across of area in Jhansi, Jalaun and Hamirpur Districts.
Second Five Year Plan Uttar Pradesh
Government of India Planning Commission
Keywords: Multi-purpose project both for irrigation and Power; Irrigation and Power; Contour Gulls and Small Channel in the Hill Districts; Minor Irrigation Scheme in the Plains of Uttar Pradesh; Short memorandum Power; Government development including The Ministry of Defence; Agriculture and community development; central and Western districts; Ramganga river Project